2005
DOI: 10.1029/2004ja010708
|View full text |Cite
|
Sign up to set email alerts
|

Cluster observations of an intense normal component of the electric field at a thin reconnecting current sheet in the tail and its role in the shock‐like acceleration of the ion fluid into the separatrix region

Abstract: [1] Measurements from the Cluster spacecraft of electric fields, magnetic fields, and ions are used to study the structure and dynamics of the reconnection region in the tail at distances of $18 R E near 22.4 MLT on 1 October 2001. This paper focuses on measurements of the large amplitude normal component of the electric field observed in the ion decoupling region near the reconnection x-line, the structure of the associated potential drops across the current sheet, and the role of the electrostatic potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
378
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 261 publications
(427 citation statements)
references
References 61 publications
48
378
1
Order By: Relevance
“…If a spacecraft flies through the ion diffusion region along the outflow direction, the expected large-scale signatures would be a reversal of plasma jetting, accompanied by a reversal of the normal component of the magnetic field. Coinciding with these reversals, one would also expect to detect portions of the quadrupolar out-of-plane Hall magnetic field (e.g., Oieroset et al 2001;Runov et al 2003;Borg et al 2005;Eastwood et al 2010aEastwood et al , 2010b) and bi-polar Hall electric field (Wygant et al 2005;Borg et al 2005;. Figure 1 displays an example of reported ion diffusion crossing by the Cluster spacecraft (Borg et al 2005) indicated by the reversals of the reconnection jets ( Fig.…”
Section: Magnetotailmentioning
confidence: 99%
“…If a spacecraft flies through the ion diffusion region along the outflow direction, the expected large-scale signatures would be a reversal of plasma jetting, accompanied by a reversal of the normal component of the magnetic field. Coinciding with these reversals, one would also expect to detect portions of the quadrupolar out-of-plane Hall magnetic field (e.g., Oieroset et al 2001;Runov et al 2003;Borg et al 2005;Eastwood et al 2010aEastwood et al , 2010b) and bi-polar Hall electric field (Wygant et al 2005;Borg et al 2005;. Figure 1 displays an example of reported ion diffusion crossing by the Cluster spacecraft (Borg et al 2005) indicated by the reversals of the reconnection jets ( Fig.…”
Section: Magnetotailmentioning
confidence: 99%
“…Later, He et al (2008b) reconstructed the magnetic field around the same null and inferred that it was moving earthward. Xiao et al (2007) discussed the same event in terms of a pair of spiral nulls of opposite polarity (also see, Runov et al 2003;Cattell et al 2005;Wygant et al 2005). Based on the orientation of the spines and fans of the null points, Xiao et al (2007) concluded that the nulls were connected by a separator.…”
Section: Plasma Phenomena As Measured In Three Dimensionsmentioning
confidence: 99%
“…The initiation and reconfiguration of magnetic topology associated with reconnection are thought to arise as a result of demagnetization of electrons within an EDR that is embedded within a much larger IDR where ions are demagnetized. Although IDRs, where Hall physics governs the magnetofluid description, have been identified by their magnetic and electric field geometry (see e.g., Wygant et al 2005;Vaivads et al 2006;Eastwood et al 2010;Hwang et al 2013), the EDR is difficult to observe because its size is of the order of a few electron inertial lengths, d e , where d e = c/ω pe and ω pe is the electron plasma frequency. Macroscopic properties of reconnection are, however, evident in reconnection jets, i.e., accelerated plasmas outside of the small diffusion region, as well as by the reorganized magnetic topology.…”
Section: Plasma Phenomena As Measured In Three Dimensionsmentioning
confidence: 99%
“…One can determine the motion and thickness of boundaries, measure the current within the tetrahedron volume and determine the dispersion relation of the local plasma waves. These techniques have been used to study the diffusion region at the magnetopause (Vaivads et al 2004), in the magnetotail (Runov et al 2003;Borg et al 2005;Wygant et al 2005;Nakamura et al 2006;Xiao et al 2006;Eastwood et al 2007) and in the magnetosheath (Phan et al 2007).…”
Section: The Sun-earth Connectionmentioning
confidence: 99%